The Effect of Job Characteristics on Organizational Commitment: The Role of Growth Need Strength in Nepali IT Companies - Saud, Tina Rawal (Journal of Business and Management Research, 2020)
Organizational commitment is one of the critical problems faced by the organizations, today. The outcomes related to commitment i.e. turnover and absenteeism can be resolved through enriched jobs. However, there is limited knowledge availability both from practical and academic aspects regarding the effect of job characteristics on organizational commitment, and keeping this perspective in mind this study examined the effect of job characteristics on organizational commitment in Nepali IT companies along with the moderating effect of growth need strength. Altogether 167 responses were collected from employees using survey questionnaire. Regression analysis and multiple moderated regression analysis were carried out to examine the hypothesized relationship. The results indicated that job characteristics had a significant positive effect on organizational commitment and among the five dimensions of job characteristic only skill variable had a non-significant effect on organizational commitment. However, the moderating effect of growth needs strength on job characteristics and organizational commitment relationship could not be established. Research implications along with the limitations of this study are discussed.